Dos movimentos sociais para o Estado : um estudo das carreiras dos ativistas ambientais no Espírito Santo - Lerbarch, Brena Costa (2015)
The dissertation discusses the relationship between social movements and State in contemporary Brazil, focusing on the entrance of movement leaders to public agencies, by occupying appointed positions. This change in the place of political acting, which can be understood as a “transit” (from civil society to State) or from the point of view of the transformation of roles (from challengers to members of the polity), reverberates on the field of activism concerned, on the decisions and policies of the public agencies involved, as well as on the activist himself. In view of this discution, we established as object of attention the impacts promoted in the individual level, aiming to investigate and analyze the transformations processed in the objective and subjective dimensions of activist leaders' careers who stepped into the State through the occupation of public sector jobs. Thus, a study of the activist careers of six leaders recognized for having acted in a specific field of militancy on Espírito Santo (Brazil) – the environmental field – and who occupied positions in public agencies was performed. The methodology used was qualitative, and the data were collected through semi-structured in-depth interviews with the leaderships and through research in other sources, such as web pages and materials given by the interviewees. The analysis were instrumentalized by the sociology of activist careers, through which we sought to reconstruct objective itineraries and subjective aspects of the political acting of the leaders. The results reveal that, in most studied cases, the admission to State has not been followed by disengagement regarding the activism developed in environmental struggles and organizations; and that the conciliation (and sometimes the articulation) of both is recurrent. However, the double role in the movement and the State was permeated by tensions, sometimes leading to conflicts and ruptures. The work allows to conclude that, even for those who remained activists in environmental movements, impacts arised from the acting in public agencies on their objective and subjective careers, being remarkable a change in the vision and in the relationship with the State, understood as a place where you can "generate contributions".